Teacher Preparedness to Implement Competency Based Curriculum in Public Primary Schools in Kinangop Sub County, Kenya - Karua, Grace Wamaitha; Manyasi, Beatrice; Kara, Augustine (International Journal of Scientific Research and Management (IJSRM), 2025)
Kenya has shifted to competency based curriculum [CBC] in order to prepare learners for the 21st Century by facilitating acquisition of competencies relevant to real life and the world of work. Teachers, being products of the content based system of education, are likely to face challenges in relation to their understanding of CBC and the applicable instructional approaches. This study therefore investigated the extent of teachers’ preparedness in the implementation of CBC with regard to teachers’ level of awareness of the tenets of CBC and teachers’ capacity to align teaching and learning approaches towards the CBC. The study used descriptive survey research design. Data were collected using a teachers’ questionnaire whose validity was determined through expert judgement. The Cronbach’s alpha coefficient of reliability for the questionnaire was 0.7. Data were analyzed descriptively using descriptive statistics. The study established that the teachers had low level of awareness on the tenets of CBC (M = 2.10, SD = 0.21). Majority 107 (66.5%) of the teachers were not trained on CBC implementation. The teachers resorted to using strategies in the old curriculum to implement the CBC. Majority 84(52.3%) were incompetent in preparing the schemes of work. The lesson plans and records of work prepared by the teachers were defective since they originated from the schemes of work. The teachers had low capacity (M= 2.42; SD = 0.26) to select appropriate teaching and learning approaches in CBC classes. Consequently, the recommended CBC teaching and learning approaches were underutilized in CBC classes. Only group work (M = 2.54, SD = 0.58) and drama (M = 2.63, SD = 0.81) were fairly utilized in the classes. The study recommended that the Ministry of Education should upscale in-service training initiatives among the teachers in order to improve teachers’ and capability in the implementation of CBC.